e-Learning Sebagai Peran Teknologi Informasi Dalam Modernisasi Pendidikan - Gani, Alcianno G. (Universitas Dirgantara Marsekal Suryadarma, 2016)
The main form in the development of human resources is education and training. However, when considering the circumstances of geography, socio-economic and cultural diversity of Indonesia, it is clear that it is no longer sufficient when only relying on traditional ways of solving alone. In the global era, as now, agree or not, want or do not want to be associated with the technology, especially information technology. This is because the technology has affected our daily lives. Therefore, we should not be blind to the technology. Many research results indicate that whoever whose late to controls the information, it's too late to precisely obtain opportunities to advance. The developments of the science of information and communication technologies have an impact on various aspects of life, including education. Distance education or can be also referred to as distance learning, have started ogled by the perpetrators of education to be one solution of educational problems above. More precisely began to be a